The Relationship of Consumption of Food and Nutritional Status with Students Achievement Academic (Case Study at the University of WR Supratman Surabaya, Indonesian) - ., Badriyah; Widari, R. Nyoman Sri; Gamal, Ahmad (Archives of Business Research, 2017)
The quality of accounting personnel is determined by the quality of the graduates of the Faculty of Economics in particular, namely accounting, where an accountant is one of the elements of the audit power has an important role. Someone who chooses the profession as an accountant has a different motivation; the perception of someone taking action against the figure accountant will affect the motivation. The method used was a correlational analytic method using a cross-sectional approach. The independent variables in this study were food consumption and nutritional status; the dependent variable in this study was students’ academic achievement. The population was student achievement among students majoring in accounting, Economic Faculty, University W.R. Supratman Surabaya 2015–2016 with simple random sampling techniques. Data collection methods used were enclosed questionnaires; data were processed by editing, coding, scoring, and tabulating. Nutritional status showed that 35 students (56.5%) were in good condition, 22 students (35.5%) were moderate, and 7 students (8%) were low. Student achievement index was very satisfying; almost half had a very satisfying achievement index value by as much as 55 students (88.7%). The results of Spearman’s correlation test statistics with 95% confidence level (α = 0.05) obtained P = 0.000 < 0.05, which means that H0 is rejected and H1 is accepted. It can be concluded that there is a relationship between food consumption and nutritional status with students’ academic achievement majoring in accounting, Economic Faculty, University W.R. Supratman Surabaya 2015–2016. This study is expected to be used as information on food consumption and nutritional status and academic achievement students, which can assist the institution in making and implementing a design system that is readily accepted in teaching for each student and can improve student achievement for the better.